RAQAMLI TA’LIM PLATFORMASINING TOPSHIRIQLARIDAN FOYDALANIB TALABALARNING KASBIY KOMPETENTLIGINI RIVOJLANATIRISH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article provides a brief overview of the features and benefits of a digital learning platform and how to use it effectively in your learning process. One of the main advantages of the digital education platform is the availability of tasks based on various criteria for academic performance and assessment of the professional competence of students, and following the criteria specified in each task serves to develop the basic professional competence of students.